Asymmetries in climate change and livestock productivity: non-linear evidence from autoregressive distribution lag mode - Khurshid, Nabila; Ajab, Salman; Tabash, Mosab I.; Barbulescu, Marinela (Frontiers in Sustainable Food Systems, 2023)
The livestock sector is extremely important to Socioeconomic growth in Pakistan, yet it is also quite vulnerable to weather changes. Climate change reduces livestock production by changing ecosystem services such as water availability, feed quality and quantity, disease outbreaks, animal heat stress, and a decline in livestock variety and breeds. Climate change has a direct impact on ecological and animal health. As a consequence of climate change, animal diseases, and infections are becoming more widespread. With the nonlinearities of climate change in the livestock industry in mind, the present study investigated the asymmetric influence of climatic and non-climatic variables on livestock productivity across Pakistan. The empirical analysis was conducted utilizing secondary time series data from 1980 to 2000. The non-linear Autoregressive Distributive Lag (NARDL) model is used to examine the asymmetric behavior of climatic variability in the livestock sector. We include CO2 emissions, mean temperature (MT), and precipitation (PERC) as climatic variables in the current study, Formatted: Subscript Formatted: Subscript along with additional control factors. Our research discovered that CO2, MT, and PREC had asymmetries in their impacts on livestock. Variations in CO2, MT, and PREC have contradictory effects on livestock productivity in the long and short term. A percent increase in LCO2 leads to a fall in livestock production insignificantly by 1.0062% for model I and significantly by 5.7613% and 5.3929% for models II and III respectively. A percent decrease in LCO2 significantly lower livestock production by 4.1739% for model I and improves livestock production by 8.5928% and 6.7901% respectively for model II and model III. A unit increase in MT significantly improves livestock productivity by 1.5520% and 0.8149% for model-II and III respectively while a unit decrease in MT insignificantly improves livestock production by 0.1316% and 0.2122% for models II and III respectively. A unit increase and decrease in PREC significantly lower and insignificantly improve livestock productivity respectively by 0.002% in both cases for model III. To protect the livestock industry from the negative effects of climate change, this study suggests that livestock producers use new environmentally friendly technologies and ecological agricultural systems.